Urban Particulate Matter–Activated Human Dendritic Cells Induce the Expansion of Potent Inflammatory Th1, Th2, and Th17 Effector Cells - Matthews, Nick C.; Pfeffer, Paul E.; Mann, Elizabeth H.; Kelly, Frank J.; Corrigan, Christopher J.; Hawrylowicz, Catherine M.; Lee, Tak H. (American journal of respiratory cell and molecular biology, 2016)
Exposure to urban particulate matter (UPM) exacerbates asthmatic lung inflammation. Lung dendritic cells (DCs) are critical for stimulating T cell immunity and in maintaining airway tolerance, but they also react to airway UPM. The adjuvant role of UPM in enhancing primary immune responses by naive cells to allergen has been reported, but the direct effects of UPM-activated DCs on the functionality of human memory CD4 T cells (Tms), which constitute the majority of T cells in the lung, has not been investigated. Blood CD1c(+) DCs were purified and activated with UPM in the presence or absence of house dust mite or tetanus toxoid control antigen. 5-(and -6)-Carboxyfluorescein diacetate succinimidyl ester-labeled blood Tms were cocultured with autologous DCs, T cell proliferation and effector function were assessed using flow cytometry, and secreted cytokines were measured by combined bead array. UPM-DCs elicited IFN-γ and IL-13 secretion and induced proliferation in Tms isolated from both allergic patients with asthma and healthy control subjects, whereas only IL-13 was produced by Tms from patients with atopic asthma stimulated by house dust mite-loaded DCs. UPM-DCs drove the expansion and differentiation of a mixed population of Th1, Th2, and Th17 cell effectors through a mechanism that was dependent on major histocompatibility class II but not on cytokine-driven expansion. The data suggest that UPM not only has adjuvant properties but is also a source of antigen that stimulates the generation of Th2, Th1, and Th17 effector phenotypes, which have been implicated in both exacerbations of asthma and chronic inflammatory diseases.